On the Boundedness of the Intrinsic Square Function on Continual Herz Spaces with Variable Exponents (European Journal of Pure and Applied Mathematics, 2025)
Our aim in this paper is to prove the boundedness of the intrinsic square function on Herz spaces with variable exponents. Firstly we define the Lebesgue spaces with variable exponent, Herz spaces with variable exponents and some basic notations. Then we give some basic lemmas and definition of continual Herz spaces. Finally we obtain the boundedness of the intrinsic square function on continual Herz spaces under some proper assumptions.
Keywords: An intrinsic square function, continual Herz spaces